Analysis of The Willingness to Pay Of Travelers at The Jungsemi Marine Tourism Village, Kendal Regency - Gultom, Iqbal S; Anggoro, T. Danny; Asih, T. Susanti; Nugraha, R. Bambang Adhitya (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
The Ministry of Maritime Affairs and Fisheries oversees Marine Tourism Village, an initiative for the growth of marine tourism. One of the Maritime Tourism Villages in Kendal Regency is Jungsemi Village, which has a beach run by Village-Owned Enterprises (BUMDes) as its main draw. This study aims to estimate the Willingness to Pay (WTP) value of beach tourism entrance tickets at Jungsemi Maritime Tourism Village so that the optimum entrance ticket price will be obtained. A dichotomous choice questionnaire was employed to collect data on the socio-economic characteristics of 79 respondents who visited the beach, with the aim of determining the average WTP value. The WTP estimation results show that respondents are willing to pay a beach entrance ticket of IDR6,700 to maintain cleanliness and natural beauty, as well as the addition of comfortable tourist facilities. This is higher than the current admission price of IDR5,000 per person. Based on a simple linear regression model, it has been demonstrated that an increase in the admission fee by IDR1,000 per individual results in a decrease of 426 visitors to the tourist destination. With current conditions, this means that an extra 20% in entry ticket prices only reduces the number of visitors by 0.56%, showing that visitor demand is relatively inelastic and hence there is still room to increase entrance ticket prices.